Role of Postpartum IUCD Insertion after C-Section - Sumera Chaudary, Saba Tufail, Abroo Fatima, Uzma Manzoor, Nosheen Maqsood, Sana Sharif (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: To evaluate the outcome of C-section with and without postpartum IUCD insertion in terms of wound infection and bleeding. Methodology: In this Randomized Control Trial, at Department of Obstetrics/Gynaecology, Allied Hospital, Faisalabad during the years 209-20, we included 302 cases (151 in each group) who fulfilled the inclusion/exclusion criteria. Two groups were formed, Group A with inserted IUCD and Group B without IUCD insertion. Bleeding and wound infection was compared in both groups within seven days of caesarean section. Results: Both groups were insignificant regarding bleeding and wound infection. 6.6%(n=10) in Group-A and 5.3%(n=8) in B Group had wound infected (p=0.627), 2.6%(n=4) group A cases and 1.3%(n=2) cases of B group were recorded with bleeding (0.410). Conclusion: Insertion of postpartum IUCD is not significantly different when compared without IUCD insertion regarding heavy bleeding and wound infection.